2010
DOI: 10.5551/jat.2931
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Plasma C-reactive Protein Levels and the Severities of Coronary and Aortic Atherosclerosis

Abstract: Aim:Limited correlations between C-reactive protein (CRP) and coronary artery disease (CAD) have been reported. Recently, MRI became a useful tool for non-invasively evaluating atherosclerotic plaques in thoracic and abdominal aortas. Methods: To elucidate the associations between plasma CRP levels and the severities of coronary and aortic atherosclerosis, we performed aortic black-blood MRI in 136 patients undergoing coronary angiography. For each patient, 9 slices of thoracic aorta and 9 slices of abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…Acute reactant hsCRP, an important marker of inflammation, appears to stimulate endothelial dysfunction and promote inflammation in the vessel wall, thus contributing to the initiation and progression of atherogenesis 13,14) and an increased risk of cardiovascular events 15,16) . Several prospective epidemiologic and randomized controlled studies of statin therapy have shown that the hsCRP level is either an independent predictor of future cardiovascular risk 7,[17][18][19] or provides additive value, together with other traditional risk factors, for predicting cardiovascular events 20,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Acute reactant hsCRP, an important marker of inflammation, appears to stimulate endothelial dysfunction and promote inflammation in the vessel wall, thus contributing to the initiation and progression of atherogenesis 13,14) and an increased risk of cardiovascular events 15,16) . Several prospective epidemiologic and randomized controlled studies of statin therapy have shown that the hsCRP level is either an independent predictor of future cardiovascular risk 7,[17][18][19] or provides additive value, together with other traditional risk factors, for predicting cardiovascular events 20,21) .…”
Section: Discussionmentioning
confidence: 99%
“…The CRP concentration was higher in patients with this angiographic degree of stenosis, showing that CRP concentration was correlated with degree of disease severity in patients with CHD. Momiyama et al, (21) Piranfar, (22) Masood et al, (23) and Lai et al, (24) arrived at similar conclusions, namely that CRP is an index of CHD severity and may reflect plaque activity in patients with CHD, and is therefore important for clinical diagnosis and evaluation CHD risk. (21)(22)(23)(24) Another study by Ciccone et al (25) found that thickening of the carotid intima media was correlated with CRP, thus indicating that inflammatory markers affect the progressivity of atherosclerosis in subjects with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 76%
“…(21) Determination of blood viscosity was by means of an Ostwald viscometer, in which the blood sample in the Ostwald tube descends by gravitation. The time of descent was recorded with a stopwatch.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Известно, что СРБ является одним из основных маркеров хронического вос-паления и непосредственно участвует в про-грессировании атеросклероза КА [18]. В одном из исследований выявлено, что висцеральная жировая ткань (ВЖТ) стимулирует синтез СРБ [19].…”
Section: таблицаunclassified